Prawo patentowe w Japonii - Jelonek, Barbara (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The purpose of this article is to presented the history of patent law in Japan, its main assumptions, as well as the steps that are envisaged for the whole procedure of obtaining a patent and protection rights. This article also contains informations provided by the Japanese Patent Office (statistics)
Keywords: prawo patentowe; własność intelektualna; własność przemysłowa; Japonia; Fukuzawa; wzory użytkowe; shinki gohatto